2008
DOI: 10.1038/emboj.2008.141
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal insulin/IGF-1 signalling control interfollicular morphogenesis and proliferative potential through Rac activation

Abstract: The lifelong self‐renewal of the epidermis is driven by a progenitor cell population with high proliferative potential. To date, the upstream signals that determine this potential have remained largely elusive. Here, we find that insulin and insulin‐like growth factor receptors (IR and IGF‐1R) determine epidermal proliferative potential and cooperatively regulate interfollicular epidermal morphogenesis in a cell autonomous manner. Epidermal deletion of either IR or IGF‐1R or both in mice progressively decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 51 publications
5
79
0
Order By: Relevance
“…In human embryonic stem (ES) cells, self-renewal and pluripotency depend on IGF2 production by human-ES cellderived fibroblast-like cells that act as a supportive niche (Bendall et al 2007). Other research groups have confirmed the important role of IGFs for a variety of stem/progenitor cells (McDevitt et al 2005, Yan et al 2006, Stachelscheid et al 2008. Interestingly, cord levels of IGFs in the newborn are positively associated with the total number of stem cells and with future cancer risk (Savarese et al 2007).…”
Section: Ir Expression and Function In Cancer Cellsmentioning
confidence: 94%
“…In human embryonic stem (ES) cells, self-renewal and pluripotency depend on IGF2 production by human-ES cellderived fibroblast-like cells that act as a supportive niche (Bendall et al 2007). Other research groups have confirmed the important role of IGFs for a variety of stem/progenitor cells (McDevitt et al 2005, Yan et al 2006, Stachelscheid et al 2008. Interestingly, cord levels of IGFs in the newborn are positively associated with the total number of stem cells and with future cancer risk (Savarese et al 2007).…”
Section: Ir Expression and Function In Cancer Cellsmentioning
confidence: 94%
“…All mouse lines used in this study have been described previously: conditional Igf1r/Insr mice (Stachelscheid et al, 2008), Igf2 -/+ (DeChiara et al, 1990), MLC2vCre (Chen et al, 1998) and Nkx2.5Cre (Moses et al, 2001). The Igf2 allele was maintained on a 129JS2 background; all other lines were on mixed and unspecified strain backgrounds.…”
Section: Micementioning
confidence: 99%
“…Due to this approach, we obtained in all four intercrossed strains (nIR −/− , nIGF-1R +/− , FoxO1ADA, and FoxO1DN) similar mortality rates of Tg2576 mice as described in the literature avoiding excessive mortality (El Khoury et al 2007;Matsubara et al 2003;Nathan et al 2005). IGF-1R lox/+ and IR lox/lox mice were generated and genotyped as described previously (Bruning et al 2000;Stachelscheid et al 2008) and crossed with synapsin-Cre (Syn-Cre) mice to achieve neuronspecific deletion. Mice which did not express APP SW or Syn-Cre served as controls.…”
Section: Animals Breeding and Genotypingmentioning
confidence: 99%